2015
DOI: 10.1039/c5dt01388g
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic studies of mesoporous nanostructured iron oxide materials synthesized by one-step soft-templating

Abstract: A combined magnetization and (57)Fe spin-echo nuclear magnetic resonance (NMR) study has been carried out on mesoporous nanostructured materials consisting of the magnetite (Fe3O4) and maghemite (γ-Fe2O3) phases. Two series of samples were synthesized using a recently developed one-step soft-templating approach with systematic variations in calcination temperature and reaction atmosphere. Nuclear magnetic resonance has been shown to be a valuable tool for distinguishing between the two magnetic iron oxide spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 44 publications
4
9
0
Order By: Relevance
“…Moreover, the blocking temperature T B shifts to about 260 K (Figure h), above which the material becomes superparamagnetic. This increase in blocking temperature is in line with reports of, e.g., Jin et al, who observed a similar shift from about 170 to about 330 K after reduction of aggregated maghemite nanoparticles to magnetite.…”
Section: Partial Transition Of Maghemite Into Magnetite (H2/ar 350 °C)supporting
confidence: 93%
See 4 more Smart Citations
“…Moreover, the blocking temperature T B shifts to about 260 K (Figure h), above which the material becomes superparamagnetic. This increase in blocking temperature is in line with reports of, e.g., Jin et al, who observed a similar shift from about 170 to about 330 K after reduction of aggregated maghemite nanoparticles to magnetite.…”
Section: Partial Transition Of Maghemite Into Magnetite (H2/ar 350 °C)supporting
confidence: 93%
“…However, above T B the thermal energy is high enough to overcome magnetic anisotropy and randomize the orientation of the magnetic domains, inducing paramagnetism. The observed temperature dependence agrees well with aggregated maghemite nanoparticles of similar crystallite sizes whereas (silica derived) hard‐templated maghemite shows a much higher blocking temperature of 340 K …”
Section: Maghemite Formation (N2 350 °C)supporting
confidence: 68%
See 3 more Smart Citations